Fatally bitten ammonites from septarian concretions of the 'Marston Marble' (Lower Jurassic, Sinemurian), Somerset, UK, and their taphonomy. Issue 1 (February 2015) - Andrew, Chris; Howe, Paddy; Paul, Chris
Abstract A small polished slab of 'Marston Marble', Lower Jurassic, from Marston Magna, Somerset, UK, contains several ammonite specimens with pieces of shell missing from the body chamber immediately in front of the last suture. The damage is visible in sagittal sections, yet its position and extent are almost identical to damage reported from several Lower Jurassic ammonite genera from the Dorset coast and elsewhere, and attributed to the trace fossil Bicrescomanducator rolli. A second cut, but unpolished slab of 'Marston Marble' shows two more ventrally damaged ammonites, one in sagittal section. The damage is interpreted as the result of predation, by a teuthoid cephalopod and affected two prey species. This is the first time ventral bite marks have been reported from sectioned ammonites. Some ammonites, but not bitten examples, have their body chambers largely filled with diagenetic calcite and were buried with the body inside. Often the calcite does not fill the full width of the body chamber, creating a false geopetal structure. As these are variously orientated with respect to bedding, the ammonites were possibly reworked before final burial. The polished slab derived from a septarian concretion. As the septarian cracks opened some ammonites were pulled apart. During shrinkage the sediment maintained a tight grip on fossils.